Application of The Odonga Ronga Kolopua Folklore to The Character of Group B Children at The Pembina Wundulako State Kindergarten - Ernawati, Andi; Puridawaty , Brigita (Kirana Publisher (KNPub), 2024)
This research aims to analyze the influence of the application of the Odonga Ronga Kolopua folklore on the character of group B children at the Pembina Wundulako State Kindergarten. The research method used was an experiment with a pretest-posttest design. The research population was all group B students at the Pembina Wundulako State Kindergarten, totaling 30 students, with a sample of 10 students using a purposive sampling technique. Data collection was carried out through observation sheets and checklists. Data analysis was carried out using SPSS 24 and paired sample t-test. The results of the research show that there is a significant influence of the application of the Odonga Ronga Kolopua folklore on the character of group B children, with a significance value (sig) of 0.002. The implication of this research is the importance of using local folklore in early childhood education to strengthen cultural identity and build sensitivity to traditional values. The suggestion put forward is that PAUD teachers and parents can utilize the Odonga Ronga Kolopua folklore in children's learning activities, and further research can explore the impact of the story on other aspects of children's development such as creativity and language skills.